Hasil Belajar Siswa Melalui Model Pembelajaran PBL Berbasis CRT (Culturally Responsive Teaching) Pada Materi Ekologi Dan Keanekaragaman Hayati Kelas VII di SMP Negeri 4 Karanganom - Zaharani, Intan; Agustina, Lina (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the learning outcomes through the application of learning models to students towards PBL based on CRT (Culturally Responsive Teaching) in class VII SMP Negeri 4 Karanganom. The approach in this study is quantitative. This type of research is True Experimental Design which uses posttest only control design. The sample used in this study was class VII F and VII G. The research data instruments were in the form of tests and observations. With the Validity Test and Reliability Test instruments with data analysis techniques of Normality Test and Homogeneity Test, t-test and learning outcomes. The results of this study indicate that the t-test results show a significant difference between the experimental class and the control class, with a significance value of 0.000 which is smaller than 0.05. This means that the null hypothesis (H0) is rejected, so it can be concluded that there is a real difference between the two classes. The conclusion of this study is that the PBL learning model based on CRT (Culturally Responsive Teaching) has an effect on student learning outcomes in the material of ecology and biodiversity in class VII.